The Quest for Synthetic Science: Carl Heinrich Becker's Reflections on University Reform and the Institutionalization of Sociology in Germany - Bas, Muhammed Fazil (ISTANBUL UNIV, FAC LETTERS, DEPT SOCIOLOGY, 2022)
German Orientalist Carl Heinrich Becker appeared as the most important cultural politician in the Prussian Ministry of Education in terms of his roles as civil servant and minister between 1916-1930. He noted the vital importance of returning to the question of culture, especially in the face of the crisis right after 1918 when Germany had been defeated in World War I and the German Empire had ceded its place to the Weimar Republic. Becker also processed the tensions of the economic, social, and political transformations Germany had experienced since the 1880s. In this context, Becker dealt primarily with the problems of German higher education, especially in his book Gedanken zur Hochschulreform [Reflections on Higher Education Reform] (1919), and stated the particularism and individualism in the political and social spheres to be the most important problems German cultural life faced. According to Becker, the lack of unity among the individual, the public, and the state at the level of civic understanding had weakened the German nation. In order to overcome this issue, university courses and sciences needed to be developed that would offer a mentality of synthesis, namely that they would grasp social, economic, and political issues as a whole, not in parts. In this framework, sociology stood out as the most important field in which the synthetic understanding of science had emerged. This article focuses on Becker's approach to the issue of culture and university reform in general and the need to institutionalize sociology as a scientific discipline in particular.
Keywords: Carl Heinrich Becker; University reform; Sociology in Germany; Institutionalization of sociology; Synthetic science; Sociology